Free-convection flow past a horizontal surface in a nanofluid with suction/injection - Mohd Adnan, Nurul Shahirah; Md. Arifin, Norihan; Bachok @ Lati, Norfifah; Mohd Nazar, Roslinda (AIP Publishing, 2016)
The present work deals with the steady free-convection boundary-layer flow past a horizontal permeable surface embedded in a porous medium filled with a nanofluid. The similarity transformation was applied to the governing equations to transform into a system of ordinary differential equations, which are then solved numerically using Runge-Kutta-Fehlberg fourth-fifth order (RKF45) method. Three types of nanoparticles which are titania (TiO2), alumina (Al2O3), and copper (Cu) in the based fluid of water are considered to investigate the effect of the nanoparticle volume fraction parameter, υ. Results are presented and discussed for the local Nusselt number, the surface velocity, the temperature profiles, and the velocity profile. It is found that the imposition of suction/injection has an impact on the velocity profiles and temperature profiles.